Activities of Kindergartens – Schools of Lithuania: External Assessment 2007 to 2011 - Simanavičienė, Loreta; Survutaitė, Dalia (Pedagogika, 2014)
As Lithuania is getting integrated into the European education dimension, the quality of education activities becomes of utmost importance. The quality of education activities in the countries of the European Union is considered to be the main priority of their education policy. The issues of quality and efficiency of education and general secondary school activities is becoming topical, and the problem of performance quality assessment arises. The kindergartens-schools of Lithuania follow the quality assessment provisions established by the National School Assessment Agency. The external assessment of performance reveals the quality of activities of kindergartens - schools, their ability to change, develop and seek solutions. The present study is the first scientific contribution towards further analysis of the kindergartens-schools performance quality. When analyzing the national assessment results of the Lithuanian kindergartens – schools performance assessed during 2007–2011 it has been established that the performance quality as to the spheres and themes was evaluated to be of the 2nd level (not bad). The analysis of strengths (+10) showed that the most often specified (eight kindergartens-schools) strengths were the cozy environment (1.3.3), and the least noted strengths (in three institutions) were grading in the teaching / learning process (2.6), grading as cognition and information (2.6.3) and personnel management (5.4). Analysis of the performance aspects to-be-further-improved (–5) showed that the most occurring recommendation (seven kindergartens-schools) for further development was the differentiation of teaching / learning (2.5.2), and the least occurring (four kindergartens - schools) – further improvement of homework system (2.3.5), grading process (5.2.1), grading in teaching / learning process (2.6), and teaching of learning skills (2.4.2). The analysis of the Lithuanian kindergartens-schools assessed during 2007–2011 heads’ attitude towards external assessment revealed that the heads of eleven assessed kindergartens - schools found the external audit to be beneficial to them and confirmed that to their opinion the external audit conducted in the institutions under them had positive effect on the institution community and that they were satisfied with the external audit carried out by the National School Assessment Agency.